Sharing views of CLIL lesson planning in language teacher education - Dario Luis Banegas (Universidad de La Sabana, 2015)
Argentina seems to favour CLIL (content and language integrated learning) as a language-driven approach in secondary and higher education. In this paper, I investigate curriculum development and lesson planning based on trainees' perceptions and lesson plans submitted to pass a module on Didactics as part of their formal initial English language teacher education. My aim is to compare what a group of trainees does in relation to the notion of CLIL as forward curriculum planning and the frameworks posited in the CLIL literature. My theoretical framework is guided by the concept of didactic transposition applied to CLIL and the literature on CLIL lessons plans drawing on teachers' voices through their plans. In this paper I discuss how language-driven CLIL was envisaged by a group of 47 trainees enrolled in a teacher education course in southern Argentina. Data emerged from a survey and lesson plans aimed at secondary-school learners for whom English was usually taught two hours a week. Results show that language-driven CLIL follows forward design; it focuses more on content than on explicit knowledge of the language, and it is aimed at revising language with older learners.